Donor-Acceptor Properties of a Single-Molecule Altered by On-Surface Complex Formation - Meier, Tobias; Pawlak, Rémy; Kawai, Shigeki; Geng, Yan; Liu, Xunshan; Decurtins, Silvio; Hapala, Prokop; Baratoff, Alexis; Liu, Shi-Xia; Jelínek, Pavel; Meyer, Ernst; Glatzel, Thilo (ACS nano, 2017)
Electron donor-acceptor molecules are of outstanding interest in molecular electronics and organic solar cells for their intramolecular charge transfer controlled via electrical or optical excitation. The preservation of their electronic character in the ground state upon adsorption on a surface is cardinal for their implementation in such single-molecule devices. Here, we investigate by atomic force microscopy and scanning tunneling microscopy a prototypical system consisting of a π-conjugated tetrathiafulvalene-fused dipyridophenazine molecule adsorbed on thin NaCl films on Cu(111). Depending on the adsorption site, the molecule is found either in a nearly undisturbed free state or in a bound state. In the latter case, the molecule adopts a specific adsorption site, leading to the formation of a chelate complex with a single Na+ alkali cation pulled out from the insulating film. Although expected to be electronically decoupled, the charge distribution of the complex is drastically modified, leading to the loss of the intrinsic donor-acceptor character. The chelate complex formation is reversible with respect to lateral manipulations, enabling tunable donor-acceptor molecular switches activated by on-surface coordination.
Keywords: atomic force microscopy; single molecule; force spectroscopy; scanning tunneling microscopy; coordination; fused donor−acceptor molecules; local contact potential difference